Legal analysis of derivative transactions in islamic economics - Widjaja, Gunawan (Edelweiss Applied Science and Technology, 2024)
The legal position regarding derivative transactions in Islamic economic practices has attracted significant attention from Islamic financial institutions such as AAOIFI and DSN-MUI. Derivative instruments can be incorporated into the sharia framework as long as they fulfil the core principles of sharia such as being free from elements of riba (interest), gharar (uncertainty), and maysir (gambling). These bodies have issued guidelines and fatwas such as the DSN-MUI fatwa No. 96/DSN-MUI/IV/2015, which permits the use of derivatives for hedging purposes under a number of strict requirements that ensure transparency and fairness and emphasizes that transactions are based on real needs and not speculation. However, implementing these legal guidelines on the ground faces various challenges. Key challenges include correctly applying derivative instruments so that they do not turn into prohibited tools of malicious speculation. Strict supervision and audit systems are needed to ensure compliance with Shariah principles on an ongoing basis, as well as ensuring transparency in the execution of transactions. In addition, in-depth training and education for Islamic finance practitioners is essential to support proper and effective implementation. Thus, the legal position regarding derivative transactions in the Islamic economy is clear and feasible to implement with strict supervision and supported by continuing education.